2002
DOI: 10.1136/jcp.55.7.508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of complete androgen blockade for 12 and 24 weeks on the pathological stage and resection margin status of prostate cancer

Abstract: Aims: To compare the pathological stage and surgical margin status in patients undergoing either immediate radical prostatectomy or 12 and 24 weeks of neoadjuvant hormonal treatment (NHT) in a prospective, randomised study. Methods: Whole mount sections of 393 radical prostatectomy specimens were evaluated: 128 patients had immediate surgery, 143 were treated for 12 weeks and 122 for 24 weeks with complete androgen blockade. Results: Histopathology revealed organ confined tumours in 40.4% of patients with clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…The proportion of pathologic organ confined disease [7][8][9][10] and negative lymph-node metastasis [7-9, 11, 12] was higher among the neoadjuvant ADT group in some trials. Although a longer duration of ADT (more than 3 months) showed better pathologic outcome in three trials, the data on recurrence and survival was not available from these studies [13][14][15]. Five trials reported the disease free survival (DFS) and none showed a significant difference in DFS [7,8,12,16,17].…”
Section: Neoadjuvant Androgen Deprivation Therapy Prior To Rpmentioning
confidence: 98%
“…The proportion of pathologic organ confined disease [7][8][9][10] and negative lymph-node metastasis [7-9, 11, 12] was higher among the neoadjuvant ADT group in some trials. Although a longer duration of ADT (more than 3 months) showed better pathologic outcome in three trials, the data on recurrence and survival was not available from these studies [13][14][15]. Five trials reported the disease free survival (DFS) and none showed a significant difference in DFS [7,8,12,16,17].…”
Section: Neoadjuvant Androgen Deprivation Therapy Prior To Rpmentioning
confidence: 98%
“…The German S3 guidelines underline, however, the adverse impact of such treatment on the histopathological workup and prognostic stratification [5]. Currently, the prognostic evaluation of patients who received neoadjuvant hormonal treatment relies only on the anatomical tumour stage and the margin status, factors that may be influenced by neoadjuvant hormonal treatment as well as the Gleason score [8,16,17]. Neoadjuvant hormonal treatment is occasionally used in multimodality approaches for high-risk tumours [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant hormonal therapy was in fact performed for 25 of the 37 patients before the operation ( table 1 ) all but one receiving maximum androgen blockage (MAB: LH-RH agonist + anti-androgens) for 1-2 months (mean 1.5 months), the single exception being given LH-RH agonist alone. Patients who had received less than 3 months' treatment were considered acceptable for inclusion because of the low likelihood of major clinical effects within this period [11][12][13] .…”
Section: Methodsmentioning
confidence: 99%
“…Since there is a likelihood that long-term hormone therapy will reduce tumor size, the present cases were limited to patients receiving such a therapy for less than 3 months, it being generally accepted that 3 months or longer are necessary for hormone effects to become evident [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%